2013
DOI: 10.1111/pedi.12096
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life in intensively treated youths with early-onset type 1 diabetes: a population-based survey

Abstract: Good glycemic control and a high level of treatment satisfaction are associated with a positive QoL in youths with early-onset type 1 diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
50
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(57 citation statements)
references
References 33 publications
4
50
3
Order By: Relevance
“…Diabetes‐specific measures are designed to cover meaningful aspects of the disease and its treatment, and hence, offer a greater depth of insight to the experiences of patients. They are also more sensitive to treatment differences …”
Section: Introductionmentioning
confidence: 99%
“…Diabetes‐specific measures are designed to cover meaningful aspects of the disease and its treatment, and hence, offer a greater depth of insight to the experiences of patients. They are also more sensitive to treatment differences …”
Section: Introductionmentioning
confidence: 99%
“…The study design of the baseline‐survey conducted 2009 to 2010 has been described in detail previously . In summary, the 840 participants of this questionnaire survey had an onset of disease during the period of 1993‐1999 when the patients were younger than 5 years old.…”
Section: Methodsmentioning
confidence: 99%
“…A multitude of cross‐sectional studies with diabetic youths have already shown that glycemic control and QoL are related to each other. A common finding is that better QoL is observed in patients with lower hemoglobin A1c (HbA1c) . To date, it is not conclusively established whether poor glycemic control results in impaired QoL or vice versa.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17] The Kindl ® questionnaire consists of 30 questions grouped under their domains related to physical and emotional well-being, self-esteem, family, friends, school and disease, resulting in a global score of 0-100. It was previously used in several studies, especially for children with chronic diseases.…”
Section: Interventionsmentioning
confidence: 99%